Marine Bioactive Peptides-Structure, Function, and Application - Chi, Chang-Feng; Wang, Bin (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
In recent years, peptides generated from various marine organisms have attracted wide attention due to their diverse chemical structures and bioactivities, including antioxidant, immune-modulating, angiotensin-I-converting enzyme (ACE)-inhibitory, hypotensive, hypolipidemic, antiviral, cytotoxic, neurotoxic, anticoagulant, antifreeze, etc. Moreover, bioactive peptides can serve as additional functional components used in health foods, nutraceuticals, bio-preservatives, cosmetics, and pharmaceuticals. The Special Issue on "Marine Bioactive Peptides-Structure, Function, and Application" aimed to collect papers on up-to-date information regarding the preparation, structural identification, activity and functional evaluation, and application of marine bioactive peptides.